Ichthyoplankton drift through fishway in large dam: effect of hydrology, seasonal patterns and larvae condition - Silva, Patricia Sarai da; Celestino, Leandro Fernandes; Assumpção, Lucileine de; Makrakis, Sergio; Dias, João Henrique Pinheiro [UNESP]; Kashiwaqui, Elaine Antoniassi Luiz; Makrakis, Maristela Cavicchioli (Taylor & Francis, 2020)
The seasonal pattern and the composition of downstream drift of fish eggs and larvae through the fish ladder of the Porto Primavera dam, located in the Upper Paraná River, Brazil, were studied. Additionally, the condition of individual larvae with regard to injuries was examined. Samples were collected monthly over three reproductive seasons at upper and lower pools at the twilight (nightfall and dawn). Ichthyoplankton densities were low, especially for eggs, and the downstream passage of fish eggs and larvae through the fish ladder was negatively correlated to water residence time of the reservoir. Highest larvae densities occurred between December and March, with highest densities in February. The ichthyoplankton abundance was similar between sites and times of day, with the predominance of partially damaged larvae (60%). Seventeen taxa were identified, especially non-migratory species. Long-distance migratory species represented less than 1% of the total. Since many migratory species have found favorable habitats for spawning and development in the tributaries of Porto Primavera Reservoir, the dispersion of larvae from these free-flowing tributaries located far from dam through reservoir may not be beneficial for their survival. At the same time, despite the low density and diversity of migratory species larvae drifting downstream from the dam, this fish ladder may have dispersive potential as long as the reservoir displays a shorter water residence time.
Keywords: fish ladder; Fish passage; larvae and eggs; migration; reservoir residence time